한국 디지털 문화유산(Digital Heritage) 관리 방안: 유럽 유로피아나(Europeana)와 한국 e뮤지엄 사례를 중심으로 - 김나현(Na Hyun Kim) (디지털콘텐츠학회논문지, 2024)
본 연구는 디지털 문화유산의 관리 현황을 분석하고 향후 한국 사례에 적용할 방안을 모색하고자 유럽의 유로피아나(Europeana)와 한국의 e뮤지엄(eMuseum)을 비교 분석하는 것을 목적으로 한다. 먼저 디지털 문화유산의 정의와 선행연구를 통해 개념을 정리한 후 유로피아나와 e뮤지엄의 운영 방식과 기능을 비교했다. 이 과정에서 SWOT 분석을 통해 각 시스템의 강점과 약점, 기회와 위협을 평가하였다. 연구 결과, 유로피아나는 유럽 전역의 광범위한 디지털 컬렉션을 보유하고 있으며, 다국어 지원, 메타데이터와 저작권 관리의 국제적 표준화, 국제 협력 부분에서 강점을 보였으며, e뮤지엄은 원본 해상도의 고화질 이미지 제공, 전문가에 의해 생성된 신뢰성 있는 정보, 공공누리 제도를 통한 자유로운 활용이 강점으로 나타났다. 두 사례 모두 재정적 지속 가능성을 위해 재정적 다각화가 필요하며 e뮤지엄은 저작권 관리의 국제 표준화, 다국어 지원 확대, 사용자 친화적 인터페이스 개발이 필요하다는 점을 제언하였다. 이러한 개선 방안을 통해 한국의 디지털 문화유산 관리의 효율성과 디지털 접근성을 향상시키고, 한국 문화유산을 전 세계에 효과적으로 알릴 수 있는 기회를 창출할 수 있을 것이다. This study analyzes the current management of digital cultural heritage in Korea by comparing Europeana, a European digital cultural heritage platform, with Korea’s eMuseum. After reviewing the concepts and previous studies on digital cultural heritage, the study compares the operational methods and functions of Europeana and eMuseum, using a SWOT analysis to assess each system’s strengths, weaknesses, opportunities, and threats. The findings reveal that Europeana excels in its extensive digital collection, multilingual support, international standardization of metadata and copyright management, and global cooperation. In contrast, eMuseum’s strengths include providing high-resolution images, expert-verified information, and free access through the Korea Open Government License (KOGL) system. Both platforms require financial diversification to ensure sustainability, and eMuseum should also focus on international copyright standardization, expanding multilingual support, and enhancing user interfaces. These improvements will boost the efficiency and accessibility of Korea’s digital cultural heritage management and help promote Korean cultural heritage globally. KCI Citation Count: 0